Teaching Development in Higher Education in Spain: the optimism of the will within a black box model. - Joan Rué Domingo; Ana Arana Navarro; María González de Audícana Amenábar; Ana Rosa Abadía Valle; Fernando Blanco Lorente; Concepción Bueno García; Amparo Fernández March (Universitat Politècnica de València, 2013)
Training in teaching at the Spanish university is a relatively new experience, except for some universities. In the past decade it has attained a larger audience due to the process of adaptation to the Higher Education European Space, which represented a profound cultural change with respect to students and their learning. However, in Spain such change had been promoted according to an institutional frame, based on technical principles, within a model of black box. Such model wishes to improve quality attending its main outcomes and ignoring the processes and the necessary training for either those who develop or are involved in it. From Vice-Chancellors to the faculty staff, they had to deal with such change without the necessary understanding of its basic conceptions and its consequent related practices. Nevertheless, three cases of different universities depict how relevant such understanding can be. They emphasize the importance of teacher training when wishing at the improvement of the processes of teaching and learning, in order to attain a better quality in the proposed training to their students.